Transpiration response of palmer amaranth (Amaranthus palmeri) to drying soil in greenhouse conditions - Cominelli, Sofia; Patrignani, Andres (Frontiers in Agronomy, 2022)
Palmer amaranth (Amaranthus palmeri S. Watson) is a troublesome weed that can result in substantial crop yield loss in irrigated and rainfed agricultural systems of the U.S. Great Plains. Transpiration responses to soil water deficit are necessary to better understand the competitive nature of Palmer amaranth against crops in limiting soil moisture conditions. The objective was to quantify the soil matric potential at which the transpiration rate of Palmer amaranth starts to decline during soil drying conditions. A greenhouse experiment consisting of six replications of well-watered and stressed plants growing in columns of a packed silt loam soil on automated load cells was established in May 2021 in Manhattan, KS. Hourly transpiration rates were computed as the difference of two consecutive mass readings. Stomatal conductance was measured every other day on the topmost fully developed leaf using a leaf porometer. Soil matric potential was estimated using a measured soil water retention curve. The stomatal conductance of plants undergoing soil drying conditions started to decrease at a soil matric potential of -120 kPa and the plant-level transpiration rate started to decrease at -176 kPa. Palmer amaranth exhibited high (246 g h-1) day-time transpiration rates when soil water was available at low tension levels (-10 to -33 kPa). In advanced stages of development, plants also exhibited nighttime transpiration that accounted for ~10% of the day-time transpiration total. Mean transpiration use efficiency of well-watered and stressed plants considering total dry biomass were similar (P=0.247), with values of 10.9 and 11.6 g kg-1, respectively. Overall, this study substantiates the competitive nature for soil water of Palmer amaranth in sub-humid and semi-arid environments and highlights the importance of early control of Palmer amaranth to minimize competition for soil moisture.